Effects of Intensive Cell Phone (Philips Genic 900) Use on the Rat Kidney Tissue - Koca, Orhan; Gökçe, Ali Murat; Öztürk, Metin Ishak; Ercan, Feriha; Yurdakul, Necati; Karaman, Muhammet Ihsan (Urology Journal, 2013)